Adapting to a global pandemic: a qualitative assessment of programmatic responses to COVID-19 in the multi-country Women’s Integrated Sexual Health (WISH) programme - Katy Footman; Pippa Page; Victoria Boydell; Megan McLaren; Sandra Mudhune (Sexual and Reproductive Health Matters, 2023)
The COVID-19 pandemic caused significant disruption to sexual and reproductive health and rights (SRHR) globally but there is little published evidence on the COVID-19 response of SRHR programmes, or lessons learned through their adaptations. To document the COVID-19 response of a global SRHR programme (the Women’s Integrated Sexual Health programme), in-depth interviews were conducted between April and July 2021 with 22 key informants from implementing partners in Sierra Leone, Ethiopia and central or regional offices, the UK Foreign, Commonwealth and Development Office and the third-party monitoring partner. Framework analysis methods were used. Several rapid COVID-19 adaptations were identified: the development of crisis management and communication teams; increased partnership and engagement with government; reduced contact and risk in service delivery; reformulated community mobilisation; flexible performance management and remote methods of quality assurance; and sharing of learnings alongside the development of new guidance and tools. Throughout the pandemic, the programme was able to continue high-quality service delivery, though equity goals proved more difficult to reach. Challenges included the continually changing environment, competing pressures on governments, burdensome reporting, and staff burnout. The pandemic response was facilitated by prior experience of health emergencies, strong government relationships, a supportive workforce and some pre-existing approaches, tools, and systems. This study has identified important lessons that can inform programming in future crises, including the need for immediate recognition of SRHR as essential, sustained support for staff, use of multiple mechanisms to reach marginalised groups, adequate funding for equity goals, and a better balance between the burden of reporting and accountability needs.